Ancient society - Morgan, Lewis Henry, 1818-1881 (Salt Lake City, UT : Project Gutenberg, 2014)
"Ancient Society: or, Researches in the lines of human progress from savagery" by Lewis H. Morgan is an anthropological work published in 1877. Building on his earlier kinship research, Morgan proposes that human societies progress through three universal stages: Savagery, Barbarism, and Civilization. He develops this theory by comparing what he calls "ethna"$1 (Binventions, discoveries, and institutions$1 (Bacross different cultures. His ideas profoundly influenced European thinkers including Marx and Engels, shaping debates about social evolution and human development that continue to resonate in anthropology today. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Ancient_Society
Release date is 2014-06-13
E-text prepared by Julie Miller, Turgut Dincer, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/American Libraries (https://archive.org/details/americana)
Keywords: Sociology; Prehistoric peoples; Civilization; Social evolution; Social structure; Political anthropology